2021
DOI: 10.1177/1934578x20985649
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antimicrobial, and Cytotoxic Activities of Leaf, Fruit, and Branch Essential Oils Obtained From Zanthoxylum nitidum Grown in Vietnam

Abstract: Zanthoxylum nitidum (Roxb.) DC is a traditional Vietnamese medicine to treat coughs, stomachache, toothache, blood stagnation, and sore throats. The essential oils (EOs) of the leaves, fruits, and stems of this plant were extracted by hydrodistillation and subjected to analysis by gas chromatography (GC)-flame ionization detector (FID) and GC-mass spectrometry (MS). The isolated EOs were then evaluated in terms of their antimicrobial activity by minimum inhibitory concentration (MIC) assay and in vitro cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The effectiveness of the antibacterial and anticancer activities of some compounds of this species have recently been scientifically confirmed (Choi et al 2008). The bioactive compounds for medical use can be found in all plant parts of Z. schinifolium (Tuyen et al 2021). However, the components of the extracts obtained from various parts of the same plant can fluctuate, leading to important compositional dissimilarities.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…The effectiveness of the antibacterial and anticancer activities of some compounds of this species have recently been scientifically confirmed (Choi et al 2008). The bioactive compounds for medical use can be found in all plant parts of Z. schinifolium (Tuyen et al 2021). However, the components of the extracts obtained from various parts of the same plant can fluctuate, leading to important compositional dissimilarities.…”
Section: Introductionmentioning
confidence: 90%
“…In previous studies, the essential oil content of Z. schinifolium fruit was reported by Iseli et al (2007) as limonene (21.63%), 4-terpineol (14.50%), and α-terpineol acetate (5.33%). Tuyen et al (2021) reported that the major components of essential leaf oil from Z. schinifolium were limonene (44.3%), β-caryophyllene (12.5%), linalool (11.0%), germacrene D (5.3%), and α-pinene (4.9%), and the major components of the essential fruit oil were n-pentadecane (34.8%), sabinene (18.3%), and n-heptadecane (4.7%), and the major components of the essential Z. schinifolium branch oil were 2-undecanone (72.3%), β-caryophyllene (5.8%), and germacrene D (4.0%). As reported in above studies the volatile components may vary depending on the parts of the same species of plants, which is also shown by the results of this study (Table 2).…”
Section: Chemical Components Of Hydrosolmentioning
confidence: 99%
See 2 more Smart Citations
“…GC-FID analysis was applied using similar conditions as those used for GC-MS analysis. 16 The GC-FID peak area was used to calculate the relative percentage of components in the essential oil, without any correction factor. Identification of the constituents was carried out by comparing the obtained retention indices (RI) and mass…”
Section: Phytochemical Screening Of Essential Oilsmentioning
confidence: 99%